Assessment of an innovative hybrid system of PVT-driven RO desalination unit integrated with solar dish concentrator as preheating unit. (15th April 2022) - Abdelgaied, Mohamed; Abdullah, A.S.; Kabeel, A.E.; Abosheiasha, H.F.
Highlights: Develop a very effective innovative system for treatment of brackish/seawater with lower power consumption. An innovative system of PVT-driven RO desalination unit coupled with solar dish concentrator was studied. Effect of solar dish concentrators as pre-heating units on the performance of RO units was studied. Saving in SPCRO-PX for the innovative system ranged between 24.33 and 35.79% for treating brackish water. Saving in SPCRO-PX for the innovative system ranged between 18.69 and 22.87% for treating seawater. Abstract: The specific power consumption in RO desalination plants is one of the most effective parameters involved in optimizing the design and operation of these plants for the treatment of brackish water and seawater. Therefore, this study aimed to simulate an innovative stand-alone desalination plant that consumes less power and is suitable for remote areas. To achieve this goal, the RO desalination unit (operated with an energy recovery device) was provided with the solar-PV panels with the thermal recovery system and the solar dish concentrator with the solar thermal receiver. The solar-PV panels were utilized to power the RO desalination unit, in addition, both the thermal recovery system of the PV panels and the solar dish concentrator with the solar thermal receiver were utilized as pre-heating units. To heat the feed water before it is pumped to the RO desalination plant, in order to reduce the specific power consumption rates. The solar pre-heating process of feed water was carried out in two successive stages; in the first stage, the feed water is heated by passing it through the thermal recovery system of the PV panels to cool it down and thus improve its performance. In the second stage, the feed water is heated by passing it through the solar thermal receiver of a solar dish condenser. The results indicated that the use of solar pre-heating units to heat the feed water has positive effects in terms of increasing the membrane permeability and decreasing the losses of fluid friction across the membranes and narrow flow channels, and this represents a positive and very important factor for reducing the rates of specific power consumption (SPCRO-PX ) in the RO desalination units with energy recovery device. Where, the saving in SPCRO-PX for utilizing the solar pre-heating unit ranged between 24.33 and 35.79% and 18.69–22.87% in the case of treating brackish water and seawater, respectively as compared to the case without solar pre-heating units.